Measuring agency costs and the value of investment opportunities of U.S. bank holding companies with stochastic frontier estimation - Joseph P. Hughes; Loretta J. Mester; Choon-Geol Moon (Rutgers University, Department of Economics, 2016)
By eliminating the influence of statistical noise, stochastic frontier techniques permit the estimation of the best-practice value of a firms investment opportunities and the magnitude of a firms systematic failure to achieve its best-practice market value - a gauge of the magnitude of agency costs. These frontiers are estimated from the performance of all firms in the industry and, thus, capture best-practice performance that is, unlike Tobins q ratio, independent of the managerial decisions of any particular firm. Using the frontier measure of performance applied to 2007 data on top-tier, publicly traded U. S. bank holding companies, we obtain evidence on market discipline: we find that higher managerial ownership at most banks tends to align the interests of insiders with those of outside owners and to be associated with improved financial performance; at most banks, higher blockholder ownership is associated with improved financial performance obtained from blockholders monitoring; and, at most banks, higher product-market concentration is associated with poorer financial performance and the so-called managerial quiet life. Using the frontier measure of investment opportunities, we find evidence that banks with relatively higher-valued investment opportunities achieve less of their potential market value, while banks with lower-valued opportunities achieve more of their potential value. In spite of their lower-valued opportunities, these banks, on average, achieve the same Tobins q ratio and, thus, appear better able to exploit their less valuable investment opportunities. Our results suggest that higher-valued opportunities may reduce managers performance pressure and provide a stronger incentive to consume agency goods.
Keywords: C58; G21; G28; 330; banking; efficiency; ownership structure; competition